PENGARUH SUDUT DATANG GELOMBANG TERHADAP KERUSAKAN UNIT LAPIS LINDUNG PEMECAH GELOMBANG - Sriyana Sriyana (KEAIRAN, 2006)
Angle of wave direction is highly influence on the amount of damage in the armour layer unit breakwater. This research is aimed at knowing in the influence of angle of wave direction toward damage in armour layer unit. There kind of angle of wave direction is used in this research. There were 0o, 15o, and 30o with employing tetrapod, cubes, and rubble mound as the armour layer. This study is carried out by means of irregular breaker waves on phisical modeling with non-overtopping condition. The result of measurements indicate that increasingly angle of wave direction 0o have largest effect to determination of the amount of damage in the armour layer unit of breakwater than 15o, and 30o.